Implementasi Health Promoting University (HPU) di Universitas Respati Yogyakartasebagai Upaya Mewujudkan Kampus Sehat, Inovatif, dan Berbasis Pemberdayaan Komunitas Akademik - Rini Pratiwi; Andreas Novaldi Wali Wungo; Markus Gelar Kumara Agni (Universitas Muhammadiyah Manado, 2025)
Health promotion program at the University is a health promotion program implemented at the higher education or college which aims to improve the health of students,employees and the community. In this study, the researcher used qualitative to find out the Implementation of Health Promoting University that has been implemented by Respati University Yogyakarta. The information obtained by the implementer was clear and to facilitate communication, HPU members used Watsapp application. Resources are still limited, both in staff and funding sources. In its implementation, HPU was assisted by the assistance of health workers and activity funds from students and parties outside the University. Members of HPU Universitas Respati Yogyakarta are still continue to support HPU programs. The SOP is still absent, and the division of tasks in HPU is in accordance with competencies. The program implementation process has gone well, although the planned target has not been 100% achieved. In terms of effectiveness, improving the cleanliness of the canteen, campus residents' concern for the environment and campus residents' concern for their own health. The Zero Tolerance Tobacco must be improved because there are still campus residents who smoke on campus and there are no strict sanctions for residents who violate.